DEVELOPMENT OF METHOD FOR DETERMINATION OF INTRINSIC VISCOSITY OF INJECTABLE DRUG WITH CHONDROITIN SULFATE - K. R. Saveleva; L. V. Pesanova; V. N. Shestakov; S. V. Poliyakov (Разработка и регистрация лекарственных средств, 2019)
The article presents data on the development of a technique for determination of intrinsic viscosity of injectable drug with chondroitin sodium sulfate. A 0.2 M solution of sodium chloride was use as a solvent to eliminate polyelectrolyte swelling. The calculated viscosity of the test solutions was determinate in the concentration range of chondroitin sulfate 4.5-20 mg /ml. The value of the intrinsic viscosity, determined for each of the tested preparations, was in the range 0.03-0.042 m3/kg.